Inherent X-Linked Genetic Variability and Cellular Mosaicism Unique to Females Contribute to Sex-Related Differences in the Innate Immune Response - Spolarics, Zoltan; Peña, Geber; Qin, Yong; Donnelly, Robert J.; Livingston, David H. (Frontiers in Immunology, 2017)
Females have a longer lifespan and better general health than males. Considerable number of studies also demonstrated that after trauma and sepsis females present better outcomes as compared to males indicating sex-related differences in the innate immune response. The current notion is that differences in the immuno-modulatory effects of sex hormones are the underlying causative mechanism. However, the field remains controversial and the exclusive role of sex hormones has been challenged. Here we propose that polymorphic X-linked immune competent genes, which are abundant in the population are important players in sex-based immuno-modulation and play a key role in causing sex-related outcome differences following trauma or sepsis. We describe the differences in X chromosome (ChrX) regulation between males and females and its consequences in the context of common X-linked polymorphisms at the individual as well as population level. We also discuss the potential pathophysiological and immune-modulatory aspects of ChrX cellular mosaicism which is unique to females and how this may contribute to sex-biased immune-modulation. The potential confounding effects of ChrX skewing of cell progenitors at the bone marrow is also presented together with aspects of acute trauma-induced de novo ChrX skewing at the periphery. In support of the hypothesis, novel observations indicating ChrX skewing in a female trauma cohort as well as case studies depicting the temporal relationship between trauma-induced cellular skewing and the clinical course are also described. Lastly, we list and discuss a selected set of polymorphic X-linked genes which are frequent in the population and have key regulatory or metabolic functions in the innate immune response and therefore, are primary candidates for mediating sex-biased immune responses. We conclude that sex-related differences in a variety of disease processes including the innate inflammatory response to injury and infection may be related to the abundance of X-linked polymorphic immune-competent genes, differences in ChrX regulation and inheritance patterns between the sexes and the presence of X-linked cellular mosaicism which is unique to females.